Efficient organic manganese(ii) bromide green-light-emitting diodes enabled by manipulating the hole and electron transport layer. Issue 34 (5th August 2021) - Jana, Atanu; Sree, Vijaya Gopalan; Ba, Qiankai; Cho, Seong Chan; Lee, Sang Uck; Cho, Sangeun; Jo, Yongcheol; Meena, Abhishek; Kim, Hyungsang; Im, Hyunsik
Abstract : A lead-free, nontoxic green-light-emitting PHOLED is successfully fabricated using a [(H2 CCHCH2 )(C6 H5 )3 P]2 MnBr4 active layer by engineering different hole and electron transport layers. Abstract : Lead-free, non-toxic transition metal-based phosphorescent organic–inorganic hybrid (OIH) compounds are promising for next-generation flat-panel displays and solid-state light-emitting devices. In the present study, we fabricate highly efficient phosphorescent green-light-emitting diodes (PHOLEDs) using the lead-free, non-toxic, zero-dimensional OIH compound [(H2 CCHCH2 )(C6 H5 )3 P]2 MnBr4 (1 ), which exhibits an emission peak at 516 nm and a long lifetime of 441 μs. The long lifetime indicates the phosphorescent emissive nature of 1 . Density functional theory calculations confirm that the narrow green emission from 1 is due to the highly localized electronic states of the valence and conduction bands. A flexible green-light-emitting phosphorescent substrate is successfully fabricated from 1 using a nylon membrane, indicating that 1 has a significant potential for use in flexible optoelectronic devices. By engineering the organic hole and electron transport layers, we achieve a highly efficient all-vacuum-deposited PHOLED with a current efficiency of 24.71 cd A −1, a power efficiency of 20.61 lm W −1, and an external quantum efficiency of 7.12%. Together, our findings will pave the way for the development of high-performance Mn(ii )-based LEDs.